ISLAMISME: KEMUNCULAN DAN PERKEMBANGANNYA DI INDONESIA - Siti Mahmudah (Aqlam: Journal of Islam and Plurality, 2018)
Abstract. This study examines the origin,  existence, and development of Islamism group in Indonesia since pre-independence until now. Islamism is a group of Muslims who are obedient to the teachings of Islam, but they are very extreme, literal,  static and rigid in understanding the teachings of Islam (Alquran), and reject to the other Muslims who disagree with Islamic ideology that they have embraced. The group of Islamism existed and emerged in Indonesia, it was not apart from the influence of the spread of Islamic teachings from al-Ikhwan al-Muslimun that was founded by Hasan al-Banna in Egypt in 1928. The group of Islamism was the first Muslim group before the other Muslim groups in Indonesia; such as the Pos-Islamism group, the Liberal Islam Group, the Moderate Islamic Group, the Progressive Islam Group. The group of Islamism in Indonesia—as al-Ikhwan al-Muslimun in Egypt who aspires to spread the ideology of Islam for all of the world—seeks  to spread  their ideology with the movement of "creeping up" for all of the area in Indonesian, since before independence until now. Islamist groups succeeded in spreading Islam and Sharia through mosques, schools, ta'lim majlis. The existence and development of Islamist groups in Indonesia today are flattered. They have very much support from the political elite. However, they are not aware that their hands are being borrowed or exploited by political elites to seize or get the  power in irrational ways. Keywords: Islamism, Emergence, Existence, Development, Indonesia. Abstrak. Studi ini membahas tentang asal usul, eksistensi dan perkembangan kelompok Islamisme di Indonesia sejak pra-kemerdekaan sampai sekarang. Kelompok Islamisme adalah kumpulan Muslim yang patuh terhadap ajaran Islam, namun mereka sangat ekstrem, literal, statis dan kaku dalam memahami ajaran Islam (Alquran), serta menolak golongan Muslim lain yang berbeda dengan faham Islam yang sudah mereka anut. Kelompok Islamisme ada dan muncul di Indonesia tidak terlepas dari pengaruh penyebaran ajaran Islam ala  al-Ikhwan al-Muslimun yang didirikan oleh Hasan al-Banna di Mesir pada tahun 1928. Kelompok Islamisme merupakan kelompok Muslim yang pertama ada sebelum adanya kelompok-kelompok Muslim lain di Indonesia; seperti kelompok Pos-Islamisme, Kelompok Islam Liberal, Kelompok Islam Moderat, Kelompok Islam Progresif. Kelompok Islamisme di Indonesia –sebagaimana al-Ikhwan al-Muslimun di Mesir yang bercita-cita menyebarkan faham berislam ke seluruh dunia—berupaya menyebarkan paham Islamisme dengan gerakan “merayap” ke seluruh bumi Indonesia sejak sebelum Indonesia merdeka sampai sekarang. Kelompok Islamisme berhasil menyebarkan faham Islam dan Syariah melalui, antara lain:  masjid-masjid, sekolah-sekolah, majelis-majelis taklim. Eksistensi dan perkembangan kelompok-kelompok Islamisme di Indonesia zaman ini sedang merasa tersanjung, karena banyak mendapat dukungan dari para elit politik. Namun sebaliknya, mereka tidak sadar bahwa tangan-tangan mereka sedang dipinjam atau pun dimanfaatkan oleh para elit politik untuk merebut atau pun mendapatkan sebuah kekuasaan dengan cara-cara yang tidak rasional. Kata Kunci: Islamisme, Eksistensi, Kemunculan,  Perkembangan, Indonesia.